2015
DOI: 10.1038/srep10016
|View full text |Cite
|
Sign up to set email alerts
|

Has upwelling strengthened along worldwide coasts over 1982-2010?

Abstract: Changes in coastal upwelling strength have been widely studied since 1990 when Bakun proposed that global warming can induce the intensification of upwelling in coastal areas. Whether present wind trends support this hypothesis remains controversial, as results of previous studies seem to depend on the study area, the length of the time series, the season, and even the database used. In this study, temporal and spatial trends in the coastal upwelling regime worldwide were investigated during upwelling seasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
133
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 67 publications
10
133
5
Order By: Relevance
“…Importantly, there is stronger agreement that significant trends of upwelling intensification are evident at higher latitude for all EBUS. Among studies excluded from the meta-analysis, either because they did not meet the strict selection criteria or because they were published after the analysis was completed, most (Di Lorenzo et al, 2005;Alves and Miranda, 2013;Barton et al, 2013;Bylhouwer et al, 2013;Stocker et al, 2013;Cropper et al, 2014;deCastro et al, 2014;Jacox et al, 2014;Sydeman et al, 2014b;Varela et al, 2015) show results consistent with the findings of Sydeman et al (2014a). Those containing seemingly contradictory results (Demarcq, 2009;Dewitte et al, 2012) add uncertainty, but do not refute the findings of the metaanalysis, as they focus on local regions, use short time series and do not add uncertainty.…”
Section: Trends In Upwelling-favorable Windssupporting
confidence: 57%
See 1 more Smart Citation
“…Importantly, there is stronger agreement that significant trends of upwelling intensification are evident at higher latitude for all EBUS. Among studies excluded from the meta-analysis, either because they did not meet the strict selection criteria or because they were published after the analysis was completed, most (Di Lorenzo et al, 2005;Alves and Miranda, 2013;Barton et al, 2013;Bylhouwer et al, 2013;Stocker et al, 2013;Cropper et al, 2014;deCastro et al, 2014;Jacox et al, 2014;Sydeman et al, 2014b;Varela et al, 2015) show results consistent with the findings of Sydeman et al (2014a). Those containing seemingly contradictory results (Demarcq, 2009;Dewitte et al, 2012) add uncertainty, but do not refute the findings of the metaanalysis, as they focus on local regions, use short time series and do not add uncertainty.…”
Section: Trends In Upwelling-favorable Windssupporting
confidence: 57%
“…Adding complexity to the picture, increases in the variability (extremes) of upwellingfavorable winds in the California Current have been observed since the late 1940s (Macias et al, 2012;García-Reyes et al, 2014), a finding consistent with increased upwelling-favorable winds during the warm months (Sydeman et al, 2014a). Less variability has been observed in the strength of upwelling winds through the year in the central Benguela and Canary Currents (Shannon and Nelson, 1996;Varela et al, 2015), though this conclusion might be influenced by a lack of studies. Clearly, further research is needed in all EBUS on changes in the timing and variability of upwelling given the influence these phenomena have on their ecosystems (Black et al, 2011;García-Reyes et al, 2014).…”
Section: Trends In Upwelling-favorable Windsmentioning
confidence: 48%
“…Cropper et al (2014) found that coastal summer wind speed increased, resulting in an increase in upwelling-favorable wind speeds north of 20 • N and an increase in downwelling-favorable winds south of 20 • N. Santos et al (2005Santos et al ( , 2012 showed that sea surface temperature (SST) was not homogeneous either along latitude or longitude and depended on the upwelling index (UI) intensity. Varela et al (2015) demonstrated opposite results worldwide depending on the length of data, season evaluated, and selected area within the same wind data set or between data sets. For the Mauritanian region, when wind stress data were used (Varela et al, 2015), a more persistent increasing trend in upwelling-favorable winds north of 21 • N and a decreasing trend south of 19 • N was determined.…”
Section: Introductionmentioning
confidence: 96%
“…Varela et al (2015) demonstrated opposite results worldwide depending on the length of data, season evaluated, and selected area within the same wind data set or between data sets. For the Mauritanian region, when wind stress data were used (Varela et al, 2015), a more persistent increasing trend in upwelling-favorable winds north of 21 • N and a decreasing trend south of 19 • N was determined.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation